2023
DOI: 10.3390/biomedicines11041198
|View full text |Cite
|
Sign up to set email alerts
|

Small Dense LDL Level and LDL/HDL Distribution in Acute Coronary Syndrome Patients

Abstract: This study aimed to determine the size and distribution of LDL and HDL particles in North African acute coronary syndrome (ACS) patients and to compare the level of small dense LDL (sdLDL) to other markers used in cardiovascular risk prediction. Methods: A total of 205 ACS patients and 100 healthy control subjects were enrolled. LDL particle size and LDL and HDL subclass distributions were measured using Quantimetric Lipoprint® linear polyacrylamide gel electrophoresis. Lipid ratios (total cholesterol, LDL cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The results of a cohort study revealed that ACS patients exhibited a significant increase in sdLDL serum concentrations compared to the healthy control group. Additionally, a Spearman correlation analysis has demonstrated a statistically significant, albeit weak, positive correlation between sdLDL levels and the AIP; r = 0.32 (p < 0.001) [30]. Previous studies have underscored the prognostic significance of the AIP in predicting adverse cardiovascular events in individuals afflicted with CAD.…”
Section: Discussionmentioning
confidence: 94%
“…The results of a cohort study revealed that ACS patients exhibited a significant increase in sdLDL serum concentrations compared to the healthy control group. Additionally, a Spearman correlation analysis has demonstrated a statistically significant, albeit weak, positive correlation between sdLDL levels and the AIP; r = 0.32 (p < 0.001) [30]. Previous studies have underscored the prognostic significance of the AIP in predicting adverse cardiovascular events in individuals afflicted with CAD.…”
Section: Discussionmentioning
confidence: 94%
“…The calculation formula was: Youden's index = Sensitivity + Specificity − 1. When Youden's index was the largest, its cut-off value was the best [29]. After calculation, the sensitivity of SUV-Max was 100% and the specificity was 66%.…”
Section: The Correlation Between Different Factors and K I -Mean And ...mentioning
confidence: 97%
“…The plasma samples were analyzed using the Lipoprint LDL System and Lipoprint HDL System (Quantimetrix Inc., Redondo Beach, CA, USA) by non-denaturing polyacrylamide gel electrophoresis. The LDL and HDL subclasses were quantified based on the measurements of LDL-C and HDL-C levels, as well as gel tube scans [65,66]. LDL subclasses included IDL-C, IDL-B, IDL-A, and LDL1-LDL7.…”
Section: Blood Collection and Lipoprotein Analysismentioning
confidence: 99%